Insights into the Mode of Action of the Sactibiotic Thuricin CD - Mathur, Harsh; Fallico, Vincenzo; O’Connor, Paula M.; Rea, Mary C.; Cotter, Paul D.; Hill, Colin; Ross, R. Paul (Frontiers in Microbiology, 2017)
Thuricin CD is a two-component bacteriocin, consisting of the peptides Trnα and Trnβ, and belongs to the newly-designated sactibiotic subclass of bacteriocins. While it is clear from studies conducted thus far that it is a narrow-spectrum bacteriocin, requiring the synergistic activity of the two peptides, the precise mechanism of action of thuricin CD has not been elucidated. This study used a combination of flow cytometry and traditional culture-dependent assays to ascertain the effects of the thuricin CD peptides on the morphology, physiology and viability of sensitive Bacillus firmus DPC6349 cells. We show that both Trnα and Trnβ are membrane-acting and cause a collapse of the membrane potential, which could not be reversed even under membrane-repolarizing conditions. Furthermore, the depolarizing action of thuricin CD is accompanied by simultaneous reductions in cell size and granularity, producing a pattern of physiological alterations in DPC6349 cells similar to those triggered by the pore-forming single-component bacteriocin Nisin A, and two-component lacticin 3147. Taken together, these results lead us to postulate that the lytic activity of thuricin CD involves the insertion of thuricin CD peptides into the membrane of target cells leading to membrane depolarization and permeabilization due to pore formation.